EFEKTIVITAS SALAT TAUBAT DALAM MENINGKATKAN KETENANGAN HATI - Ahmad Rusdi (Psikis : Jurnal Psikologi Islami, 2016)
The purpose of this study is examine the prayers of repentance effect on sobriety. Respondents of this study are 49 Students. This research was conducted by using a simple experiment. Researchers have explained how the prayers of repentance to be done during one week. sobriety was measured before and after one week. sobriety consists of two aspects, composure (al-suku>n) and conviction (al-yaqi>n).  After  prayers  of  repentance  for  one  week,  sobriety  on  respondents  increased significantly (Sig 0,00) both aspects, al-suku>n  (Sig 0,00) and al-yaqi>n (Sig 0,036). Some details of  the  results  of  this  study  showed  unique  results.  This  study  concluded  that  multidimensional prayers of repentance will increase sobriety periodically.